Blame ratings fall on erratic policies, Duterte told - Yap, DJ. (2017)
The 18-point drop in Mr. Duterte's net satisfaction rating showed that Filipinos were growing frustrated over the President's persistent erratic demeans
Keywords: Duterte administration -- Criticism; Duterte administration -- Political stability